2015
DOI: 10.9775/kvfd.2015.13516
|View full text |Cite
|
Sign up to set email alerts
|

Süt Sığırlarında Bulanık Mantık Tabanlı Karar Destek Sistemi

Abstract: Various methods have been developed to achieve the most suitable solution in the face of challenges of constantly changing living conditions. Fuzzy logic is one of these methods and frequently preferred by researchers in recent years. Fuzzy logic is based on artificial intelligence modeling the information that includes uncertainty in the most appropriate mindset of people, especially in the decision making process. It also offers flexible and realistic perspectives to people. In this study, a fuzzy logic-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
3
0
2
Order By: Relevance
“…However, it has been observed that mental abilities such as intuition, non-monotonic and reasonable reasoning cannot be resolved with the classical logic understanding; therefore different studies have been made. The Decision support system is the one of those alternatives [24,29] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it has been observed that mental abilities such as intuition, non-monotonic and reasonable reasoning cannot be resolved with the classical logic understanding; therefore different studies have been made. The Decision support system is the one of those alternatives [24,29] .…”
Section: Discussionmentioning
confidence: 99%
“…Artificial intelligence approaches like Fuzzy Logic can be initiated the expert's vision since they are included the information of experts. Because of this feature, fuzzy logic can be an alternative method for animal science related studies [24] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(9) Selejtezéstámogatás. Előzőhöz hasonló rendszert fejlesztettek ki fuzzy logikán alapuló döntéstámogató rendszerként Holstein Fríz tehenek szaporodási paramétereinek és tejhozam-nyilvántartásainak felhasználásával (Akilli et al, 2015, idézi Balhara et al, 2021 a 305 napra korrigált tejhozam (305 DMY), szervizidőszak (SP), ellési intervallum (CI), mesterséges termékenyítés (AI) és száraz időszak (DP) mint bemeneti paraméterek felhasználásával. A döntéstámogató rendszer kimeneti paramétere az osztályozási döntés, amely a szakértői döntéssel nagyon jól korrelált.…”
Section: Mi-algoritmusokat Alkalmazó Specifikus Gazdálkodási Területe...unclassified
“…A fuzzy logika ebben a rendszerben az automatikus bírálat bizonytalanságának kiküszöbölésére alkalmazzák. Ugyancsak fuzzylogikaalapú szakértői döntéstámogató rendszer támogatja Holstein tehenek osztályozását reprodukciós és tejtermelési paraméterei alapján (Akilli et al, 2015, idézi Balhara et al, 2021, illetve egészségügyi menedzsmentjét (Pimpa et al, 2019, idézi Balhara et al, 2021.…”
Section: Alkalmazási Területe Az áLlati Termék-előállításbanunclassified